Early life history of tropical seagrasses enhalus acoroides (L.f.) royle and thalassia hemprichii (EHRENB.) aschers. off cape Bolinao (NW Philippines) - Cayabyab, Napo M.; David, Laura T. (Quezon City Marine Science Institute, College of Science, University of the Philippines Diliman, 2007)
The study aims to contribute to the understanding of recruitment biology of tropical seagrasses Enhalus acoroides and Thalassia hemprichii, the most dominant, widely distributed, and sexually prolific SE Asian seagrass species. In particular, the distribution, abundance and the dynamics of the newly recruited individuals in Cape Bolinao were determined using transect-quadrat method and reconstruction (ageing) technique.
Thesis (M.S. Marine Science)--University of the Philippines Diliman
Keywords: Seagrasses -- Philippines -- Cape (Bolinao).